2005
DOI: 10.1038/sj.ejcn.1602338
|View full text |Cite
|
Sign up to set email alerts
|

Effects of probiotics on the severity of experimental acute pancreatitis

Abstract: Objective: This study was designed to evaluate the effects of probiotics on the severity of experimental acute pancreatitis. Design: Experimental study. Setting: Experiments were done in a laboratory at Haydarpasa Numune Teaching and Research Hospital. Subjects:A total of 50 Wistar rats were randomly divided into five groups. Interventions: Group 1 was control group. Group 2 received an intraperitoneal injection of a 20% solution in 0.15 mol/l NaCL. Group 3 was injected NaCL and fed with probiotics. Acute panc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 20 publications
0
28
1
2
Order By: Relevance
“…They found that the histopathologic scores of acute necrotizing pancreatitis were significantly lower. A study published by Muftuoglu et al [55] confirmed that enteral feeding completed with probiotics reduced the severity of acute experimental pancreatitis based on histological analysis. Another paper by van Minnen et al [56] demonstrated that probiotics reduced duodenal bacterial overgrowth of potential pathogens, resulting in reduced bacterial translocation to extra-intestinal sites, including the pancreas.…”
Section: Probioticsmentioning
confidence: 80%
“…They found that the histopathologic scores of acute necrotizing pancreatitis were significantly lower. A study published by Muftuoglu et al [55] confirmed that enteral feeding completed with probiotics reduced the severity of acute experimental pancreatitis based on histological analysis. Another paper by van Minnen et al [56] demonstrated that probiotics reduced duodenal bacterial overgrowth of potential pathogens, resulting in reduced bacterial translocation to extra-intestinal sites, including the pancreas.…”
Section: Probioticsmentioning
confidence: 80%
“…Two recent studies of rats analyzed the impact of pretreatment with synbiotics on the severity of experimental acute pancreatitis. Pretreatment with synbiotics reduced the severity of histopathologic findings 27 and reversed the pancreatitis-induced increase in endotoxemia and transaminase levels 28 compared with saline or metronidazole.…”
Section: Discussionmentioning
confidence: 96%
“…The excellent results of using probiotics in experimental pancreatitis models were promising initially [55][56][57][58][59]. Mangiante et al significantly reduced infected necrosis rate using Lactobacillus plantarum [55], and a study by van Minnen et al from Utrecht demonstrated that probiotics reduced significantly even the late-phase mortality [58].…”
Section: Composition Of Enteral Nutritionmentioning
confidence: 95%